Integrating DevOps into Software Engineering Education: A Laboratory Experience - Reis, Lucas; Castro, Fernando; Diniz, Hudson; Mendes, Benedito; Silva, Luis; Viana, Davi (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Teaching DevOps in undergraduate courses represents innovation, and it is important to prepare students for the dynamic challenges of software development. This experience involves a practical SE Lab on the concept and implementation of DevOps practices, aiming to bring students from UFMA closer to the implementation of these practices, providing solutions to meet the daily demands of the code development process. Our methodology addressed the creation of a learning environment based on the 4C/ID instructional design model, where we developed and implemented three scenarios for the application of DevOps practices through the construction of a CRUD application, using tools such as Next.js, Node.js, Prisma ORM, GitHub, GitHub Actions and PostgreSQL. To measure our methodology, we collected feedback from students at the end of the project. Through the analysis of this data, it was possible to compare the levels of previous experience and those acquired. We also observed a significant improvement in the understanding of the tools used, in addition to a gain of more than 30% in DevOps practices. Our work contributes to the implementation of a methodological approach that not only teaches DevOps practices, but also prepares students to face real challenges in the software development life cycle.